2003
DOI: 10.1289/ehp.5726
|View full text |Cite
|
Sign up to set email alerts
|

Fenitrothion: toxicokinetics and toxicologic evaluation in human volunteers.

Abstract: An unblinded crossover study of fenitrothion 0.18 mg/kg/day [36 times the acceptable daily intake (ADI)] and 0.36 mg/kg/day (72 X ADI) administered as two daily divided doses for 4 days in 12 human volunteers was designed and undertaken after results from a pilot study. On days 1 and 4, blood and urine samples were collected for analysis of fenitrothion and its major metabolites, as well as plasma and red blood cell cholinesterase activities, and biochemistry and hematology examination. Pharmacokinetic paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 4 publications
1
28
0
Order By: Relevance
“…MNP, which is also contained in diesel exhaust emissions, has potential adverse effects on the reproductive systems in mammals and birds. Fenitrothion at doses of 0.18 and 0.36 mg/kg per day was administered to 12 human volunteers for 4 days (Meaklim et al, 2003). Pharmacokinetic parameters could only be determined at the high dosage, because the blood levels of fenitrothion at the low dosage were below the detectable level.…”
Section: Absorption Metabolism and Excretion In Laboratory Animals Amentioning
confidence: 99%
“…MNP, which is also contained in diesel exhaust emissions, has potential adverse effects on the reproductive systems in mammals and birds. Fenitrothion at doses of 0.18 and 0.36 mg/kg per day was administered to 12 human volunteers for 4 days (Meaklim et al, 2003). Pharmacokinetic parameters could only be determined at the high dosage, because the blood levels of fenitrothion at the low dosage were below the detectable level.…”
Section: Absorption Metabolism and Excretion In Laboratory Animals Amentioning
confidence: 99%
“…In 12 human volunteers given 0.36 mg/kg/day fenitrothion in capsules for 4 days, absorption was rapid, metabolism was extensive, and excretion was rapid (415). Of the administered fenitrothion, 67-76% was eliminated in urine as 3-methylnitrophenol equivalents after the first and fourth dose.…”
Section: 4223mentioning
confidence: 99%
“…Bouchard et al (2003) assessed the health risk of workers exposed to malathion by measuring metabolites (malathion mono-and dicarboxylic acids) excreted in their urine. Meaklim et al (2003) reported the toxicokinetics and a toxicologic evaluation in volunteers dosed with fenitrothion. They suggested accumulation of the OP, but the oxon metabolite was not detected and no significant abnormalities in biochemical or hematologic monitoring were observed.…”
Section: Influence Of Organophosphate Pesticides On Humansmentioning
confidence: 99%